Striatal Lacunar Infarction in a Late Preterm Infant Born to a Mother with Active Peripartum SARS-CoV-2 Infection - Christoph Hochmayr; Marlene Hammerl; Ira Winkler; Gisela Schweigmann; Ursula Kiechl-Kohlendorfer; Elke Griesmaier; Anna Posod (Hindawi Limited, 2023)
Background. The current literature suggests that neonatal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections generally have a mild course. Data on how in utero exposure to maternal infection affects neonatal health outcomes are limited, but there is evidence that neurological damage to the fetus and thromboembolic events may occur. Case Presentation. We describe the case of a late preterm infant, who presented with striatal lacunar infarction in the neonatal period, born to a mother with active peripartum SARS-CoV-2 infection. Diagnostic workup did not identify risk factors apart from the maternal SARS-CoV-2 infection. Repeated reverse transcription-polymerase chain reaction (RT-PCR) tests for SARS-CoV-2 using oropharyngeal swab specimens of the patient were negative. IgG, but not IgM antibodies against spike protein S1 receptor-binding domain (S1RBD) epitope were detectable in umbilical cord blood and neonatal serum collected at 48 hours of life. Anti-SARS-CoV-2 total antibody titers against nucleocapsid protein in umbilical cord blood were negative. Conclusions. Bearing in mind a possible association of in utero exposure to SARS-CoV-2 and neonatal thromboembolic events, neonatologists should be aware of these complications even in well-appearing preterm infants.